2019
DOI: 10.3390/atmos10070388
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Near-Inertial Wind Stress in Typhoon and Typhoon-Induced Oceanic Near-Inertial Kinetic Energy in the Upper South China Sea

Abstract: The correlation of near-inertial wind stress (NIWS) in typhoon and typhoon-induced oceanic near-inertial kinetic energy (NIKE) in the upper South China Sea (SCS) is investigated through reanalysis data and an idealized typhoon model. It is found that the typhoon-induced oceanic near-inertial currents are primarily induced by the NIWS, which may contribute to about 80% of the total NIKE induced by typhoon. The intensities and distributions of NIWS in most typhoons are consistent with the magnitudes and features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…17b) usually indicates the occurrence of a synoptic or mesoscale atmospheric event, such as the passage of a TC, and it shows that the synoptic atmospheric events occur more frequently during the winter monsoon. Figure 17c other TCs passing through this area fail to trigger significant NIKE, which may be attributed to the difference of TCs characteristics Cao et al, 2018;Li et al, 2019;Zhang et al, 2021) Overall, our analyses show that the variability of NIWSM (and hence NIKE) in the SCS can, to a large extent, be explained by a combination of seasonal intrusions of cold surges from the temperate zone in boreal winter, and TCs from tropical Pacific in boreal summer and autumn.…”
Section: Synoptic Activities In the Scsmentioning
confidence: 77%
“…17b) usually indicates the occurrence of a synoptic or mesoscale atmospheric event, such as the passage of a TC, and it shows that the synoptic atmospheric events occur more frequently during the winter monsoon. Figure 17c other TCs passing through this area fail to trigger significant NIKE, which may be attributed to the difference of TCs characteristics Cao et al, 2018;Li et al, 2019;Zhang et al, 2021) Overall, our analyses show that the variability of NIWSM (and hence NIKE) in the SCS can, to a large extent, be explained by a combination of seasonal intrusions of cold surges from the temperate zone in boreal winter, and TCs from tropical Pacific in boreal summer and autumn.…”
Section: Synoptic Activities In the Scsmentioning
confidence: 77%
“…Strong NIOs are generated in the mixed layer during the passage of TCs (e.g. D 'Asaro, 1995;Shay et al, 1998;Sanford et al, 2011;Guan et al, 2014;Li et al, 2019). After the passage of TCs, most of NIKE in the mixed layer can be imparted into thermocline and deeper layer through near-inertial internal waves (Geisler, 1970;D'Asaro, 1995;Alford and Gregg, 2001;Jiang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Direct observations of NIM under TC conditions are very sparse (Hou et al, 2019;Hu et al, 2020;Ma et al, 2019;Sun et al, 2011Sun et al, , 2012Wang et al, 2019). Simulations have scientific utility in aiding the interpretation of field data (Guan et al, 2014;Jeon et al, 2019;Kung & Gan, 2020;Li et al, 2019;Liu et al, 2015;Price, 1981;Price et al, 1994;Tsai et al, 2008;Xu et al, 2019;Yang et al, 2015). Irrespective of the model applied, the wind stress parameterization is the most critical factor, determining most of the uncertainties in WPI and NIEs (Jiang et al, 2005;Klein et al, 2004;Rath et al, 2013;Rimac et al, 2013).…”
mentioning
confidence: 99%
“…For example, appropriate interpolations of wind stress have been suggested in ocean general circulation models (OGCMs), in terms of both time steps and spatial grids, to avoid filtering out wind stress variances in the near-inertial band (Jing et al, 2015(Jing et al, , 2016. Moreover, NIMs are variable under differing TC wind field conditions, largely because of variations in intensities and translation speeds of the TCs (Geisler, 1970;Kung & Gan, 2020;Li et al, 2019;Price, 1981). It has been reported that when the TC translation speeds ( 𝐴𝐴 𝐴𝐴ℎ ) increase by 10%, the corresponding values for NIE increase by 38% (Xu et al, 2019).…”
mentioning
confidence: 99%